English Spatial Verbs and Their Vietnamese Equivalents - Nguyễn Thị Hồng Đức (2005)
This thesis is designed to investigate English spatial verbs and their Vietnamese equivalents in cognitive semantic perspective. Via this analysis, the study aims at presenting some commonly used English spatial verbs, investigating their syntactic as well as their semantic features and the similarities between English spatial verbs and their Vietnamese equivalents are considered. Finally, the spatial cognition between English and Vietnamese people across languages playing am important role for the implications in teaching, learning and the English language is dealt with.